Lugares de vida a vida, a vida nos espaços: Oswaldo Lamartine de Faria e a perspectiva da experiência (1940-1970) - Silva, Maria Samara da (2019)
The potiguar's writer Oswaldo Lamartine de Faria have been recognized, by his pairs and researchers as an important source for the history of the seridó's region. On this research besides the investigation of this connection other special relations and this consequences on the life of the author and his intellectual life have been researched. Besides other spaces we highlighted the cities of Natal, Rio de Janeiro and the farms of Lagoa Nova e Acauã. Our sources were the books Encouramento e Arreios do Vaqueiro do Seridó (1969); Sertões do Seridó (1980); Ferro de Ribeiras do Rio Grande do Norte (1984); Notas de Carregação (2001) all written by Lamartine, and the books organized by Natércia Campos, Em Alpendres d’ Acauã: Uma conversa com Oswaldo Lamartine (2001) e De Cascudo para Oswaldo (2005), besides four fragments of letters from 1994. The concepts ‘experience’ and ‘topophilia’, as defined by Yi-fu Tuan have been applied to understand the connection between the author and the many spaces analyzed, and the many approaches of the concept of ‘landscape’ of Gaston Bachelard, Yi-Fu Tuan and Simon Schama. With that it was possible to deduce the hypothesis that the many spatial experiences of Lamartine have direct and indirect impact on the description of landscapes and spaces on the books of Lamartine. This study have been conducted using the discourse methodology of Michael Pecheux and Eni Orlandi and it's thesis have been used in order to analyze the immediate context of Lamartine, the construction of a discourse about a man and his relation with spaces. As a result of the investigation we have comprehended that by the means of experimentation of the political figure and the contact the legacy of his father, Juvenal Lamartine and all the tragic events of his family that Oswaldo Lamartine start to create his affection for the Seridó region, and based on that the definition of a Sedidoense identity. Besides that it's possible to point out the fact that spatial experiences on many levels exists on the work of Lamartine, those point to a necessity of physical contact and visual appreciation in order to define his affection for the Seridó. Every space that has been occupied had it's own importance to the construction of it's personality and his work. It's possible to visualize that he is driven by the feeling of missing, not only the space, but the lifestyle based on a connection between human and nature. The landscape on the texts is the fusion between imagination, experience and the knowledge acquired of tradition, built upon since the 20th century of the Northwestern region of Brazil.